The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1089/scd.1.1998.7.413
|View full text |Cite
|
Sign up to set email alerts
|

Alternatives to Animal Sera for Human Bone Marrow Cell Expansion: Human Serum and Serum-Free Media

Abstract: The increasing use of cultured human cells in clinical trials is highlighting the need for alternatives to media containing animal sera that are typically used to support these cultures. Perfused cultures of BM mononuclear cells (MNC) were used to evaluate animal sera alternatives with respect to the output of primitive, progenitor, and stromal cells. A serum level of 20% was optimal, and this could be provided by FBS alone or by a mixture of horse serum (HoS) and FBS, but not by HoS alone. Allogeneic human pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 45 publications
(34 reference statements)
0
33
1
1
Order By: Relevance
“…Many studies have been performed to try and substitute the animal serum with human autologous or allogeneic serum or with synthetic media, but have not usually produced satisfactory results. [13][14][15] The addition of the PL has been suggested previously, [16][17][18] but the exact determination of hMSC yield starting from a reduced number of nucleated cells to reach clinically relevant numbers has never been shown previously.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been performed to try and substitute the animal serum with human autologous or allogeneic serum or with synthetic media, but have not usually produced satisfactory results. [13][14][15] The addition of the PL has been suggested previously, [16][17][18] but the exact determination of hMSC yield starting from a reduced number of nucleated cells to reach clinically relevant numbers has never been shown previously.…”
Section: Discussionmentioning
confidence: 99%
“…Replacement of FCS in expansion of BMSCs has been discussed controversially. Positive effects on the formation of fibroblast colony-forming units and proliferation rates have been reported when human serum was used with and without additional mitogenic growth factors [Anselme et al, 2002;Stute et al, 2004], whereas Koller et al [1998] found decreased support for expansion of human MSCs when both autogenous and allogenic human serum were used. Koller et al [1998] and Kuznetsov et al [2000] reported a reduction in bone formation by human MSCs cultivated using human serum.…”
Section: Discussionmentioning
confidence: 99%
“…Shigeno ve Ashton [29] OS'un FBS'dan daha üstün oldu unu söylerken, Anselme ve Yamamoto [30,31] OS ve FBS ile kültüre ettikleri MKH' lerde benzer ekilde sonuçlar elde ettiler. Koller, Kuznetsov ve Yamaguchi [32][33][34] gibi di er baz ara t r c lar ise FBS ile daha iyi sonuçlar rapor ettiler. Y lmaz ve ark.…”
Section: Tarti Maunclassified